Composition of Ingredients in Syubhah Semi Processed Food, Trust and Purchase Behavior - A Conceptual Framework - Rahman, Reezlin (Archives of Business Research, 2018)
The paper aims to reviews the growing dimension of Halal food industry, whereby consumers nowdays tend to purchase Syubhah semi processed food due to the lack of knowledge on composition of ingredients, wholesomeness, labeling and certification. An extensive review of the current literature reveals that limited holistic studies on Syubhah semi processed food exist. This study, therefore, aims to fill this gap by proposing a conceptual framework for syubhah semi processed food. This study develops a conceptual framework explaining consumer intention formation by underpinned with the theory of planned behavior which consist of attitude toward behavior, subjective norm, perceived behavioral control, intention and behavior. This study not only has implications for future research, but also provides useful information for academician and practitioners in the Halal food industries.